Intelligent machine-type communication and network for 6G system - Xu CHEN; Zhiqing WEI; Zhiyong FENG; Miao PAN (物联网学报)
With the rapid development of smart city,smart manufacturing and other industries,machine-type communication has gained much attention of academia and industry.The extent of function integration and intelligence of machine-type communication network has become increasingly high,which imposes more stringent requirements on network delay,reliability,number of connected devices,peak rate,security and scalability.Based on analyzing the change of performance requirements,key technology and corresponding network architecture of machine-type communication network in 4G,5G to future 6G system,the intelligent sensing-communication-computation integrated network architecture was proposed for 6G machine-type communication network.